Tyler Tavernier: capstone - Tavernier, Tyler, artist (Colorado State University. Libraries, 2014)
The artist's statement: Throughout my time at Colorado State, my art has changed dramatically. Coming in I thought I would have to have the most technically sound work using the most impressive of conventions. Today however, I have found my own style while also realizing the importance for individualism and originality. I've noticed the importance of simplicity in the graphic design industry so my style has become a mixture of simple layouts and typography complimented with fun and colorful imagery and illustration. One thing the teachers and design professionals have said was organization is the biggest part of a successful piece, especially in typography. That is one area I have learned that will stick with me all through my career. Type today is one of the most common forms of artistic design and now having made two typefaces of my own and working with them everyday, I understand the importance for them in our daily lives as well as in my own personal portfolio. While typography is important, the more illustrative designs are also a large part of my designs. In a number of posters and logos I have designed, the imagery is what brings the audience in. Those illustrations need to work well with the text to help the reader better understand the purpose of the poster or logo. All these different traits and conventions I have learned through my time at CSU have helped me to hone in my skills, while also allowing me to find my own unique artistic style and lead me on a path to start my career.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.